Effect of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and its toxic metabolites on the physicochemical property of the liposomal membrane in relation to their cytochrome P-450 inhibition - Das, N.P. (2012)
10.1016/0009-3084(92)90067-Y